Comparative Analyses of Full-Length Transcriptomes Reveal Gnetum luofuense Stem Developmental Dynamics - Hou, Chen; Lian, Huiming; Cai, Yanling; Wang, Yingli; Liang, Dongcheng; He, Boxiang (Frontiers in Genetics, 2021)
Genus Gnetum, of which the majority species are pantropical liana, have broad industrial uses including for string, nets, and paper production. Although numerous studies have investigated anatomical structures during stem development, the underlying molecular mechanisms that regulate this developmental trajectory in Gnetum species remain poorly understood. A total of 12 full-length transcriptomes were generated from four stem developmental stages of an arborescent representative of this genus, Gnetum luofuense, using Oxford Nanopore Technologies. The results of this analysis reveal a total of 24,151 alternative splicing (AS) and 134,391 alternative polyadenylation events. A remarkably dynamic pattern of AS events, especially in the case of intron retentions, was found across the four developmental stages while no dynamic pattern was found among transcript numbers with varied poly(A) sites. A total of 728 long non-coding RNAs were also detected; the number of cis-regulated target genes dramatically increased while no changes were found among trans-regulated target genes. In addition, a K-means clustering analysis of all full-length transcripts revealed that primary growth is associated with carbohydrate metabolism and fungi defense, while secondary growth is closely linked with photosynthesis, nitrogen transportation, and leaf ontogenesis. The use of weighted gene co-expression network analysis as well as differentially expressed transcripts reveals that bHLH, GRF, and MYB-related transcription factors are involved in primary growth, while AP2/ERF, MYB, NAC, PLAZ, and bZIP participate in G. luofuense stem secondary growth. The results of this study provide further evidence that Nanopore sequencing technology provides a cost-effective method for generating full-length transcriptome data as well as for investigating seed plant organ development.